Overtraining
Over training (staleness, over fatigue, chronic fatigue, overt raining syndrome) is a rather usual problem among athletes. The physiological homeostasis of an over trained athlete's body has become disturbed. Regulatory mechanisms of the body can not return back to the balance during the one or two days which is a normal recovery time. At first the over training state can be mild, and if an athlete rests, his body recovers fast. Later it may be more severe, and an athlete will be exhausted. The exhaustion is typical for experienced endurance athletes, who usually react in this way. Overtraining-like states can also be induced by mental, social, economical and environmental stress. These factors together with physical training cause total stress which influences on the body. Stress can be caused by both positive and negative psychological factors. These may be e.g. holiday, vacation, personal achievement, change in residence, school or job, change in social and recreational habits, financial problems, divorce, trouble at school, trouble with the law, death or birth in the family. Physiological factors cause stress as well. This kind of factors may be e.g. travel, sleep loss, races, changes in training, environmental changes (altitude, humidity, temperature), illness, injury, menstrual cycle or pregnancy. Highly motivated athletes have to keep in mind that the balance between training, other stressors and recovery has to be right, i.e., they have to periodisize their training in the right way. If there is an uncompleted recovery time after exercises, fatigue starts to accumulate and after a few days or weeks symptoms of over training with a drop in performance will arise. As a result, recovery may take weeks or months. Symptoms and signs of over training vary from athlete to athlete. The symptoms and signs are due to changes in the function of the autonomic nervous system, hormonal status, immunological parameters and other physiological and musculoskeletal changes of the body. Typically, an athlete feels tiredness and fatigue and notices a drop or stagnation in performance despite of continuing training.